Bioaccessibility of (poly)phenolic compounds of raw and cooked cardoon (Cynara cardunculus L.) after simulated gastrointestinal digestion and fermentation by human colonic microbiota. (May 2017) - Juániz, Isabel; Ludwig, Iziar A.; Bresciani, Letizia; Dall'Asta, Margherita; Mena, Pedro; Del Rio, Daniele; Cid, Concepcion; de Peña, María-Paz
Highlights: Only 2% of (poly)phenols (CQAs) in raw cardoon remain bioaccessible after digestion. Cooked cardoon had 60–67% CQA and luteolin derivatives bioaccessible after digestion. Colonic microbiota has a high catabolic activity on cardoon (poly)phenols. 3-(3′-Hydroxyphenyl)propionic acid is the most abundant colonic catabolite of cardoon. Catabolic pathways for degradation of cardoon CQAs in the colon are proposed. Abstract: A total of 17 (poly)phenolic compounds have been quantified in the free and bound fraction of raw, olive oil fried, sunflower oil fried and griddled cardoon ( Cynara cardunculus L.). Caffeoylquinic acid derivatives (CQAs), particularly 5-CQA, were the major compounds. The bioaccessibility of (poly)phenols after gastrointestinal digestion and fecal fermentation (24 h) was studied. Heat treatment exerted a positive effect on the bioaccessibility of (poly)phenols. In raw cardoon, only 2% of the total amount of (poly)phenolic compounds was still bioaccessible after gastrointestinal digestion, while in cooked cardoon samples, between 60 and 67% of the total amount of (poly)phenolic compounds remained unmodified. An important microbial metabolic activity was observed during the fecal fermentation, which resulted in a complete degradation of CQAs after 5 h and in the formation of different catabolites. 3-(3′-hydroxyphenyl)propionic acid was by far the most abundant catabolite produced. Catabolic pathways for colonic microbial degradation of CQAs of cardoon have been proposed.